Novel dispersion compensation method for cross-coupling measurement in PM-PCF based on OCDP - Jin, Jing; Wang, Shu; Song, Jingming; Song, Ningfang; Sun, Zuoming; Jiang, Man (Optical fiber technology, 2013)
•Inter-mode chromatic dispersion coefficient of PM-PCF is simulated and measured for the first time.•A dispersion compensation method in frequency-domain is proposed for OCDP result.•Coupling strength and spatial resolution can be recovered simultaneously with high accuracy.•Only raw data of interference signal and dispersion coefficient are utilized in compensation. For polarization maintaining photonic crystal fiber (PM-PCF), the cross-coupling measurement can be severely affected by interferogram broadening, due to the large inter-mode chromatic dispersion. In this paper, a novel dispersion compensation method is proposed to mitigate the influence, including a frequency domain algorithm and investigation of the dispersion coefficient for a phase packet in algorithm. A numerical simulation and measurement of birefringence as a function of wavelength reveal that the dispersion coefficient in PM-PCF is much larger than that in PANDA-PM fiber. After compensation, the accuracy of coupling strength measured can be restored and spatial resolution is improved. Experiments show the compensation provides high accuracy with average relative error less than 0.31% and spatial resolution improved 4.1times.